PERANCANGAN LEMARI PENYIMPANAN TOOLING YANG ERGONOMIS DI SECTION MACHINING PADA PROSES KERJA CNC MILLING DI PT AMTEK ENGINEERING BATAM - Zareta Akbar, Fiqih; Zetli, Sri (LPPM Universitas Putera Batam, 2023)
PT Amtek Engineering Batam is a manufacturing company that has a vision that emphasizes quality and productivity in order to remain superior in today's global business competition. PT Amtek Engineering Batam has a machining section that functions to manufacture component or part tooling, assembly components, automotive and machine auxiliary tools with various work processes, namely CNC wirecut, CNC milling, EDM, grinding and jig grinding processes. The basic materials used are copper, hard rass, high speed steel, aluminum, DC 11, Carbide and ASP 23 to produce tooling components which are an important part of stamping machines. Section machining has a make to order production system, where in one working day there are different requests and needs. Apart from that, other things also shappened when lifting the dies to the mazzak CNC milling conveyor, workers used a hoist crane, where when installing the elbows on the dieshoe the worker's body position was squatting so that from interviews conducted with several workers, workers often complained of pain in the workers' feet and hands . The problems above can be solved by creating a good work environment using the 5S method then conducting MSDs questionnaires to find out workers' pain complaints and measuring worker body anthropometry data to find percentile data from workers then designing tooling cabinets using Autocad by looking at the results of measurement data anthropometry. The result of this research is an ergonomic tooling cabinet design